1962
DOI: 10.1139/v62-130
|View full text |Cite
|
Sign up to set email alerts
|

BIOSYNTHESIS OF SUGARS FOUND IN BACTERIAL POLYSACCHARIDES: PART I. BIOSYNTHESIS OFL-RHAMNOSE

Abstract: Azotobacter indicil~iz was grown on ~nedia which contained D -g l~~~~e -l -c " ,The radioactive polysaccharides produced were hydrolyzed and the specific activities of the isolated D-glucose and L-rhamnose were measured. The sugars were degraded and the distribution of activity in the individual carbon atoms was determined.The results suggest that some L-rharnnose is formed froin D-glucose by a pathway which involves the breakdown of the glucose carbon slceleton.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0
1

Year Published

1963
1963
2000
2000

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
0
7
0
1
Order By: Relevance
“…Various enzymatic methods have been described 111, although in recent years attention has also been paid to chemical methods [2,31. The regeneration of NAD' from NADH formed by alcohol dehydrogenase has been shown to be important in the development of sensitive immunoassays [4 -61.…”
mentioning
confidence: 99%
“…Various enzymatic methods have been described 111, although in recent years attention has also been paid to chemical methods [2,31. The regeneration of NAD' from NADH formed by alcohol dehydrogenase has been shown to be important in the development of sensitive immunoassays [4 -61.…”
mentioning
confidence: 99%
“…Investigating L-rhamnose synthesis by a streptococcus, Southard, Hayashi & Barkulis (1959) also found that this monosaccharide attained a higher specific activity when D-[6-14C]glucose was the precursor than when D-[1-14Clglucose was the precursor. On the other hand, Watkin & Neish (1961) and Jones et al (1962) made the opposite observation for L-rhamnose synthesis in buckwheat and Azotobacter indicum respectively. Apart from differences in hexose metabolism in these organisms, the contributions of two pathways for the biosynthesis of L-rhamnose, varying from one organism to another, would also account for these observations.…”
Section: Procedures For Incorporation Experimentsmentioning
confidence: 97%
“…We found that, for degradation of acetaldehyde, oxidation to acetate followed by the Schmidt reaction gave better and more consistent yields of products than did the iodoform reaction. Jones et al (1962) enumerate the several published degradation schemes for L-rhamnose. Degradation according to our Scheme 1 is probably as simple and as satisfactory in terms of yields as any of them, and gives information on 14C-labelling that is sufficient for many investigations of rhamnose biosynthesis.…”
Section: Procedures For Incorporation Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In either case, when C14-labelled possible precursors are considered or used to determine the biosynthetic pathway, a procedure whereby the products may be degraded in some detail is essential. Recently, Jones and associates have reported on the biosynthesis of rhamnose and a heptose in a bacterial species in which they describe in some detail the degradation of these particular sugars (9).…”
mentioning
confidence: 99%